Proceedings of the 2014 Conference on Interactive Entertainment 2014
DOI: 10.1145/2677758.2677780
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Cybersickness

Abstract: The uptake of new interface technologies, such as the Oculus Rift have generated renewed interest in virtual reality especially for private entertainment use. However, long standing issues with unwanted side effects, such as nausea from cybersickness, continue to impact on the general use of devices such as head mounted displays. This in turn has slowed the uptake of more immersive interfaces for computer gaming and indeed more serious applications in training and health. In this paper we report a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
286
2
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(314 citation statements)
references
References 20 publications
11
286
2
15
Order By: Relevance
“…The postural instability theory is based on the idea that one of the primary behavioral goals of humans is to maintain postural stability, and therefore, prolonged postural instability results in motion sickness symptoms (Riccio and Stoffregen, 1991). Finally, "the most longstanding and popular explanation for cybersickness" is the sensory conflict theory (Davis et al, 2014), which is based on the premise that discrepancies among the senses regarding the body's orientation and motion cause a perceptual conflict that the body does not know how to handle (LaViola, 2000).…”
Section: Cybersicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…The postural instability theory is based on the idea that one of the primary behavioral goals of humans is to maintain postural stability, and therefore, prolonged postural instability results in motion sickness symptoms (Riccio and Stoffregen, 1991). Finally, "the most longstanding and popular explanation for cybersickness" is the sensory conflict theory (Davis et al, 2014), which is based on the premise that discrepancies among the senses regarding the body's orientation and motion cause a perceptual conflict that the body does not know how to handle (LaViola, 2000).…”
Section: Cybersicknessmentioning
confidence: 99%
“…Davis et al (2014) identified three categories of factors that affect cybersickness-individual factors, device factors, and task factors. Individual factors include aspects specific to each user, such as age (Reason and Brand, 1975), gender (Biocca, 1992), preexisting illness (LaViola, 2000), and posture (Riccio and Stoffregen, 1991).…”
Section: Cybersicknessmentioning
confidence: 99%
“…Davis et al investigated a condition they term cybersickness [2] in analogy to motion sickness. They consider a range of options for the cause of these problems, delay among them.…”
Section: Acceptable Delaymentioning
confidence: 99%
“…However, these systems all have in common the same potential problems when it comes to motion sickness and discomfort when using the VR solutions [2]. An important source of these problems is delay.…”
Section: Introductionmentioning
confidence: 99%
“…The daily rating form will ask participants questions regarding their VR experiences including a singleitem assessing 'Cybersickness' [58], their level of 'Immersion' in the VR experience [59], and the length of their VR experience. Participants will also be given the opportunity to provide any additional information about their VR utilization experience via three open-ended question, i.e., likes, dislikes, symptoms, and additional comments.…”
Section: ) Daily Rating Formmentioning
confidence: 99%